Predictive biomarkers for 5‐ALA‐PDT can lead to personalized treatments and overcome tumor‐specific resistances - Maria Mastrangelopoulou; Mantas Grigalavicius; Tine H. Raabe; Ellen Skarpen; Petras Juzenas; Qian Peng; Kristian Berg; Theodossis A. Theodossiou (Cancer Reports, 2022)
Abstract Background Photodynamic therapy (PDT) is a minimally invasive, clinically approved therapy with numerous advantages over other mainstream cancer therapies. 5‐aminolevulinic acid (5‐ALA)‐PDT is of particular interest, as it uses the photosensitiser PpIX, naturally produced in the heme pathway, following 5‐ALA administration. Even though 5‐ALA‐PDT shows high specificity to cancers, differences in treatment outcomes call for predictive biomarkers to better stratify patients and to also diversify 5‐ALA‐PDT based on each cancer's phenotypic and genotypic individualities. Aims The present study seeks to highlight key biomarkers that may predict treatment outcome and simultaneously be exploited to overcome cancer‐specific resistances to 5‐ALA‐PDT. Methods and Results We submitted two glioblastoma (T98G and U87) and three breast cancer (MCF7, MDA‐MB‐231, and T47D) cell lines to 5‐ALA‐PDT. Glioblastoma cells were the most resilient to 5‐ALA‐PDT, while intracellular production of 5‐ALA‐derived protoporphyrin IX (PpIX) could not account for the recorded PDT responses. We identified the levels of expression of ABCG2 transporters, ferrochelatase (FECH), and heme oxygenase (HO‐1) as predictive biomarkers for 5‐ALA‐PDT. GPX4 and GSTP1 expression vs intracellular glutathione (GSH) levels also showed potential as PDT biomarkers. For T98G cells, inhibition of ABCG2, FECH, HO‐1, and/or intracellular GSH depletion led to profound PDT enhancement. Inhibition of ABCG2 in U87 cells was the only synergistic adjuvant to 5‐ALA‐PDT, rendering the otherwise resistant cell line fully responsive to 5‐ALA‐PDT. ABCG2 or FECH inhibition significantly enhanced 5‐ALA‐PDT‐induced MCF7 cytotoxicity, while for MDA‐MB‐231, ABCG2 inhibition and intracellular GSH depletion conferred profound synergies. FECH inhibition was the only synergism to ALA‐PDT for the most susceptible among the cell lines, T47D cells. Conclusion This study demonstrates the heterogeneity in the cellular response to 5‐ALA‐PDT and identifies biomarkers that may be used to predict treatment outcome. The study also provides preliminary findings on the potential of inhibiting specific molecular targets to overcome inherent resistances to 5‐ALA‐PDT.